2011
DOI: 10.2478/s13533-011-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

U-Pb ID-TIMS age of the Tiksheozero carbonatite: expression of 2.0 Ga alkaline magmatism in Karelia, Russia

Abstract: Abstract:The Tiksheozero carbonatite in northern Russian Karelia is a transitional type between alkaline ultramafic -carbonatitic and alkaline gabbroic suites. The complex is dominated by pyroxenite with a variety of subordinate mafic and ultramafic phases and nepheline syenite. Carbonatite occurs in a main central body and in veins. In this study we have obtained a reliable age for the complex by single grain ID-TIMS U-Pb analyses of zircon and baddeleyite. The age of 1999 ± 5 Ma is important because it place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
5
0
6
Order By: Relevance
“…According to U Pb single zircon and baddeleyite ID TIMS dating, the carbonatites of the Tiksheozero Intrusion define an age of 1999 ± 5 Ma (Corfu et al, 2011). This is well consistent with the results of local SHRIMP II U Pb baddeleyite date of 1999 ± 12 Ma (Rodionov et al, 2014).…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…According to U Pb single zircon and baddeleyite ID TIMS dating, the carbonatites of the Tiksheozero Intrusion define an age of 1999 ± 5 Ma (Corfu et al, 2011). This is well consistent with the results of local SHRIMP II U Pb baddeleyite date of 1999 ± 12 Ma (Rodionov et al, 2014).…”
Section: Introductionsupporting
confidence: 60%
“…Thus, our data showed that the crystallization of the Elet'ozero intrusive complex at 2086 ± 30 Ma pre sumably predated the formation of the adjacent 2.0 Ga old Tiksheozero ultramafic-alkaline complex with carbonatites (U Pb zircon and baddeleyite dating (Corfu et al, 2011;Tichomirowa et al, 2013;Rodio nov et al, 2014). At the same time, this does not exclude that these complexes were derived from a sin gle long lived magmatic center, as supposed by Bogachev et al (1976) and Shchiptsov et al (2007).…”
Section: Problems Of Isotope Dating Of Zirconmentioning
confidence: 83%
See 1 more Smart Citation
“…[Rukhlov et al, 2015]). К возрасту 2.0 и 2.5 млрд лет «карбонатитовых» цирконов из пробы К13-206 близок возраст карбонатитов из таких известных комплексов, как Фалаборва (Phalaborwa), Бушвельд, Каапвальский кратон (~2.06 млн лет [Wu et al, 2011], Тикшеозеро (Tiksheozero) и Сиилинярви (Siilinjärvi), Карелия, Балтийский щит (~2.0 и ~2.6 млрд лет млрд лет [Corfu et al, 2011;Tichomirowa et al, 2012]), кратона Слэйв (~2.6 млрд лет [Villeneuve, Relf, 1998]). При этом фиксируются хорошие соответствия не только возраста, но и параметров Hf изотопии, в то время как для «карбонатитовых» цирконов из пробы М08-16-1 совпадений даже по возрасту с известными данными нет (рис.…”
Section: Figureunclassified
“…Рис 1. Размещение интрузий щелочно-ультраосновной с карбонатитами формации и формации агпаитовых нефелиновых сиенитов [4] Промышленные минералы Фенноскандинавского щита В мировой практике используется большая группа полезных ископаемых под названием «��-industrial minerals» (промышленные минералы). Под индустриальными минералами подразумевают обширную группу полезных ископаемых, т. е. все минеральное сырье, которое человек извлекает из недр, кроме энергетических видов сырья, металлов, воды и самоцветов, и может использовать в промышленности благодаря определенным физическим и химическим свойствам [2,53].…”
unclassified